2018
DOI: 10.1016/j.nmd.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo-controlled phase 3 trial of an antisense oligonucleotide, drisapersen, in Duchenne muscular dystrophy

Abstract: This 48-week, randomized, placebo-controlled phase 3 study (DMD114044; NCT01254019) evaluated efficacy and safety of subcutaneous drisapersen 6 mg/kg/week in 186 ambulant boys aged ≥5 years, with Duchenne muscular dystrophy (DMD) resulting from an exon 51 skipping amenable mutation. Drisapersen was generally well tolerated, with injection-site reactions and renal events as most commonly reported adverse events. A nonsignificant treatment difference (P = 0.415) in the change from baseline in six-minute walk dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 58 publications
(109 reference statements)
1
66
0
3
Order By: Relevance
“…The limitations of currently available outcome measures have been made apparent by our collective experience in DMD, where multiple therapeutic trials have already taken place and are ongoing. Several publications on these trials have reported that the variability of the primary outcome measure (the 6‐minute walk distance) within the study population was larger than anticipated . Unanticipated high variability can greatly impact the interpretability of trial results, and we may not discover until the end of the trial that we are unable to agree upon whether the absence of a statistically significant effect is due to underpowering or true ineffectiveness of the intervention.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The limitations of currently available outcome measures have been made apparent by our collective experience in DMD, where multiple therapeutic trials have already taken place and are ongoing. Several publications on these trials have reported that the variability of the primary outcome measure (the 6‐minute walk distance) within the study population was larger than anticipated . Unanticipated high variability can greatly impact the interpretability of trial results, and we may not discover until the end of the trial that we are unable to agree upon whether the absence of a statistically significant effect is due to underpowering or true ineffectiveness of the intervention.…”
mentioning
confidence: 90%
“…Several publications on these trials have reported that the variability of the primary outcome measure (the 6-minute walk distance) within the study population was larger than anticipated. 8,9 Unanticipated high variability can greatly impact the interpretability of trial results, and we may not discover until the end of the trial that we are unable to agree upon whether the absence of a statistically significant effect is due to underpowering or true ineffectiveness of the intervention. The inability of a trial to answer its prospective scientific question carries multiple costs, including loss of participant time, consumption of limited investigator resources, and potential divisiveness within a rare disease field where collaboration is instrumental to success.…”
mentioning
confidence: 99%
“…The DMD care consideration guidelines have been updated due to recent advances in the diagnosis of DMD and the emergence of novel treatments, including genetic and molecular therapies. [3][4][5][6][7][8][9][10] Currently, DMD is treated with orally administered steroids, which suppress the infiltration of inflammatory cells into the muscle. 11,12 However, there are several problems with steroidal treatments, particularly with their safety profile in paediatrics.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with those of the DMD114117 and DMD114044 studies. 19,31 Data from natural history studies demonstrated that it can be difficult to observe significant treatment effects on the measures that were used as secondary outcome in this study after a period of only 48 weeks, 22,30,32,33 while the current study only had a 24 week treatment period. In addition, the 24 week treatment period was not sufficient to reach steady state drisapersen tissue levels.…”
Section: Discussionmentioning
confidence: 81%
“…However, in the phase 3 study, 16% of the injection site reactions remained unresolved upon study close. 31 The progressing injection site reactions were one of the reasons that drisapersen did not reach approval.…”
Section: Discussionmentioning
confidence: 99%